Morphometry of the crab Hexapanopeus schmitti (Decapoda : Xanthoidea) on the northern coast of the state of São Paulo, Brazil - Fumis, Patricia B.; Fransozo, Adilson; Bertini, Giovana; Braga, Adriane A. (Revista de Biologia Tropical, 2007)
A morphometric study of the xanthoid crab Hexapanopeus schmitti was carried out, using the allometric method. Samples were taken monthly for two years (1998-1999) in the Ubatuba region, northern coast of São Paulo, Brazil. Sex and size were assessed for each specimen, and all crabs were measured to obtain their carapace width (CW) and length (CL), abdomen width (AW) of females, major cheliped propodus length and height (PL and PH), and gonopod length (GL) of males. A total of 301 crabs were analyzed, 209 males and 92 females. The CWs of the crabs ranged from 2.5 to 9.8 mm for males and from 2.8 to 9.4 mm for females. The relative growth equation (y=ax(b)) based on the relationship between GL and CW suggested that males reach their morphological sexual maturity near 6.1 mm CW. In females, the estimated size at 50 % maturity was 4.8 mm CW, based on the relationship of AW vs. CW. Males reach larger sizes than females, which probably favors their ability to guard the females during courtship. In approximately 83 % of the crabs (n= 371), disregarding sex, the right cheliped was larger.
Keywords: relative growth; Xanthoidea; heterochely; Hexapanopeus schmitti